CXCR4 has a dual role in improving the efficacy of BCMA-redirected CAR-NK cells in multiple myeloma - Moles, Michael W.; Erdlei, Henry; Menzel, Lutz; Massaro, Marialucia; Fiori, Agnese; Bunse, Mario; Schrimpf, Moritz; Gerlach, Kerstin; Gudipati, Venugopal; Reiser, John; Mathavan, Ketan; Goodrich, Jodie P.; et al. (Frontiers in Immunology, 2024)
Multiple myeloma (MM) is a plasma cell disease with a preferential bone marrow (BM) tropism. Enforced expression of tissue-specific chemokine receptors has been shown to successfully guide adoptively-transferred CAR NK cells towards the malignant milieu in solid cancers, but also to BM-resident AML and MM. For redirection towards BM-associated chemokine CXCL12, we armored BCMA CAR-NK-92 as well as primary NK cells with ectopic expression of either wildtype CXCR4 or a gain-of-function mutant CXCR4R334X. Our data showed that BCMA CAR-NK-92 and -primary NK cells equipped with CXCR4 gained an improved ability to migrate towards CXCL12 in vitro. Beyond its classical role coordinating chemotaxis, CXCR4 has been shown to participate in T cell co-stimulation, which prompted us to examine the functionality of CXCR4-cotransduced BCMA-CAR NK cells. Ectopic CXCR4 expression enhanced the cytotoxic capacity of BCMA CAR-NK cells, as evidenced by the ability to eliminate BCMA-expressing target cell lines and primary MM cells in vitro and through accelerated cytolytic granule release. We show that CXCR4 co-modification prolonged BCMA CAR surface deposition, augmented ZAP-70 recruitment following CAR-engagement, and accelerated distal signal transduction kinetics. BCMA CAR sensitivity towards antigen was enhanced by virtue of an enhanced ZAP-70 recruitment to the immunological synapse, revealing an increased propensity of CARs to become triggered upon CXCR4 overexpression. Unexpectedly, co-stimulation via CXCR4 occurred in the absence of CXCL12 ligand-stimulation. Collectively, our findings imply that co-modification of CAR-NK cells with tissue-relevant chemokine receptors affect adoptive NK cell therapy beyond improved trafficking and retention within tumor sites.